New Insights Into the Role of Cav2 Protein Family in Calcium Flux Deregulation in Fmr1-KO Neurons - Castagnola, Sara; Delhaye, Sébastien; Folci, Alessandra; Paquet, Agnès; Brau, Frédéric; Duprat, Fabrice; Jarjat, Marielle; Grossi, Mauro; Béal, Méline; Martin, Stéphane; Mantegazza, Massimo; Bardoni, Barbara; et al. (Frontiers in Molecular Neuroscience, 2018)
Fragile X syndrome (FXS), the most common form of inherited intellectual disability and a leading cause of autism, results from the loss of expression of the Fmr1 gene which encodes the RNA-binding protein FMRP (Fragile X Mental Retardation Protein). Among the thousands mRNA targets of FMRP, numerous encode regulators of ion homeostasis. It has also been described that FMRP directly interacts with Ca2+ channels modulating their activity. Collectively these findings suggest that FMRP plays critical roles in Ca2+ homeostasis during nervous system development. We carried out a functional analysis of Ca2+ regulation using a calcium imaging approach in Fmr1-KO cultured neurons and we show that these cells display impaired steady state Ca2+ concentration and an altered entry of Ca2+ after KCl-triggered depolarization. Consistent with these data, we show that the protein product of the Cacna1a gene, the pore-forming subunit of the Cav2.1 channel, is less expressed at the plasma membrane of Fmr1-KO neurons compared to WT. Thus, our findings point out the critical role that Cav2.1 plays in the altered Ca2+ flux in Fmr1-KO neurons, impacting Ca2+ homeostasis of these cells. Remarkably, we highlight a new phenotype of cultured Fmr1-KO neurons that can be considered a novel cellular biomarker and is amenable to small molecule screening and identification of new drugs to treat FXS.